Kesan tiga pembolehubah binaan ke atas kesukaran sesuatu soalan penyelesaian masalah matematik - Mat Baok, Saiman (1987)
Much research on problem solving in mathematics has been carried out in western countries with the aim of determining variables that make a mathematics question to become more difficult to oe solved. This research is done also for the same reason, but it is limited to only three variables namely 'step', 'supertious information', and 'cue'. Determining the variables that contribute to the difficulty of a mathematics question i s necessary because it can help a learner to consider some proper steps that should be taken to overcome those difficulties. This research is done using a factorial experiment design. The sample consists of three questions of different types (arithmetic, algebra and geometry) presented in eight forms. The testing instruments were 496 new students of Universiti Pertanian Malaysia from various Diploma 1 programmes, in the July semester, 1984/85. This research produced a result similar to that of Nesher (1976) in Israel, that is the variables 'step' and 'superflous information' influence the difficulty of mathematics problems. However, the finding of this research showed that 'step' made the question more difficult co solve than 'superflous information', whereas Nesher's (1976) finding indicated the reverse. Both findings confirmed that 'cues' did not contribute to the difficulty of the questions used.